The plot thickets - Henry, Julia, 1962- (Henry, Julia, 1962- Garden Squad mystery., 2022)
While cleaning up the historic Goosebush Cemetery, Lilly Jayne stumbles upon the body of Whitney Dunne-Bradford, the conniving custodian of the graveyard, and must dig up the dirt on the real killer when the homicide inquiry suddenly targets an old friend.